URGENT X-RAY DIAGNOSTICS OF INTRACRANIAL PYOINFLAMMATORY OTORHINOSINUSOGENIC COMPLICATIONS - I. S. Piskunov; Yu. A. Shcherbuk; A. A. Krivopalov; A. N. Rubin; I. E. Glaz’Ev; E. A. Nekhaeva (Вестник хирургии имени И.И. Грекова, 2016)
An analysis of the results of X-ray CT and MR-imaging was made in 46 patients aged from 13 to 78 years old. The patients were admitted to multifield hospitals in Kursk at the period from 2005 to 2015. The research included the nasal cavity, paranasal sinuses, mastoid and pyramid of the temporal bones and the brain. The study could be repeated with bolus contrast medium infusion. The condition of the patients was evaluated in dynamics at intervals of 5-7 days and these data was associated with clinical picture. The authors presents a complex of symptoms and an algorithm of differentiated X-ray diagnostics of diseases of the ENT organs and the main nosological forms of pyoinflammatory diseases of arachnoid membrane and substances of the brain.